Chickpea and Chestnut Flours as Non-Gluten Alternatives in Cookies - Marta Torra (Foods, 2021)
This study proposes the use of a mix composed of chickpea flour and chestnut flour in cookies, aiming to improve their acceptability. Cookie properties and nutritional value were also analysed. The gluten-free cookies were made by using different mixes of chickpea and chestnut flours (0:100, 25:75, 50:50, 75:25, 100:0). Dough rheology and cookie dimensions, texture, external colour and acceptability were evaluated. The presence of the chestnut flour increased the values of G’ and G”, but reduced the loss factor (tan δ) when compared with the doughs made with chickpea flour. Chestnut flour also decreased the diameter and the spread ratio of the cookies, while increasing the hardness and darkening of the cookies. Furthermore, adding chestnut to the flour mixture increased the nutritional quality of the cookies by adding unsaturated fatty acids and fibre. The use of reduced percentages of chestnut flour (25%) resulted in masking the off-flavour of the chickpea flour, which improved the cookie’s acceptability without significantly changing the dough rheology, cookie dimensions, hardness, or lightness.